Validation of a B-type natriuretic peptide as a prognostic marker in pneumonia patients: a prospective cohort study - Yu Hashimoto; Daisuke Usuda; Ryusho Sangen; Emiri Muranaka; Yoshitsugu Iinuma; Tsugiyasu Kanda (BMJ Open)
Objectives To validate a B-type natriuretic peptide (BNP) as a prognostic marker in pneumonia patients.Design A prospective cohort study.Setting Kanazawa Medical University Himi Municipal (a 250-bed community hospital in Himi-shi, Toyama-ken, Japan).Participants All patients diagnosed with pneumonia by the physician and admitted to our hospital between 1 January 2012 and 31 March 2015 whose BNP levels had been determined in the first 24 h of admission. A total of 673 patients were enrolled. Of these, BNP levels were measured for a total of 369 patients on admission.Intervention After enrolment, baseline, demographic, clinical and laboratory characteristics including levels of suspected prognostic markers for pneumonia proposed in previous papers, were collected. All patients were followed up until discharge. During analysis, they were divided into categories as follows: community-acquired pneumonia (CAP), aspiration pneumonia (AP), healthcare-associated pneumonia (HCAP) and pneumonia with acute heart failure (PAHF). A univariate and multivariable Cox-regression analysis were applied to each parameter to identify predictors of death. Three cut-off points, namely 40, 100 and 200 pg/mL, as well as the mean, were applied when comparing BNP levels.Main outcome measures 30-day mortality.Results Of the 369 patients finally included, 137 were diagnosed with CAP, 122 with AP, 74 with HCAP, and 36 with PAHF. In the univariate analysis, BNP levels (mean, cut-off points 100 pg/mL and 200 pg/mL, p<0.01, respectively) were associated with death in CAP, and similar situation was found for BNP (cut-off points 200 pg/mL, p<0.05) in AP, but not for HCAP, or PAHF. In multivariable Cox-regression analysis, BNP remained an independent mortality predictor (HR 10.01, 95% CI 1.32 to 75.7, p=0.03) in CAP.Conclusions BNP levels may be a useful single prognostic marker for CAP. Further research for validation is warranted.